The Role of Bokavirus and Metapneumovirus in Development Acute Respiratory Infections in Hospitalized Patients in 2011-2014 years in Penza Region - I. A. Malova; I. P. Baranova (LLC "Diagnostics and Vaccines", 2016)
The article presents the results of a comparative analysis of the clinical data, laboratory and instrumental examination methods in patients with bokavirus (HBoV) and metapnevmovirus (HMPV) infections, hospitalized in the infectious disease Department of MSU № 59 Zarechnyj sity Penza region. From 713 patients with verified diagnosis with 42 (5.89%) PCR revealed metapnevmovirus infection, at 18 (2.52%) bokavirus, at 34 (4.77%) mixed infection, most often by HBoV on and HMPV were children up to 7 years, were accompanied by lesions of the upper and lower respiratory tract infections, fever, intoxication, adenopathy.